Health sciences schools students’ knowledge about human papillomavirus (HPV) - Mendonça, Paula (2019)
Introduction - According to the World Health Organization (WHO), human papillomavirus (HPV) is the most frequent viral infection of the reproductive tract, with a high prevalence in the class of young people under 25 years, who doesn’t reveal much knowledge about it. For so, it’s fundamental to collect new data about it with an exploratory study. Objectives - To describe the knowledge of students in health technology courses, using surveys technique with REDCap application monitoring.